2015
DOI: 10.1039/c4ta05231e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and conduction mechanism of the lithium superionic conductor Li10+δGe1+δP2−δS12

Abstract: The lithium diffusion pathway in the LGPS structure visualized through MEM analysis assisted in elucidating the conductivity pathway changes with temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
203
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(233 citation statements)
references
References 21 publications
(28 reference statements)
25
203
2
Order By: Relevance
“…The doped O atoms occupied vertices of the tetrahedra located at the centers of the tunnels along the c-axis, in which lithium atoms are distributed (Figure 6). These positions of the doped O atoms and the lowering of the conductivity of LSiPSO in comparison to that of the original LGPS phase supported the assumption that the tubes along the c-axis are the primary conduction pathways for lithium ions, as has also been proposed by experimental research as well as theoretical studies (Kwon et al, 2015;Wang et al, 2015). With respect to electrochemical stability, the doped oxygen is expected to increase it.…”
Section: Structure Analysissupporting
confidence: 57%
See 1 more Smart Citation
“…The doped O atoms occupied vertices of the tetrahedra located at the centers of the tunnels along the c-axis, in which lithium atoms are distributed (Figure 6). These positions of the doped O atoms and the lowering of the conductivity of LSiPSO in comparison to that of the original LGPS phase supported the assumption that the tubes along the c-axis are the primary conduction pathways for lithium ions, as has also been proposed by experimental research as well as theoretical studies (Kwon et al, 2015;Wang et al, 2015). With respect to electrochemical stability, the doped oxygen is expected to increase it.…”
Section: Structure Analysissupporting
confidence: 57%
“…Note that the superionic conductor LGPS exhibits a conductivity of 1.2 × 10 −2 S cm −1 at room temperature, which is comparable to or even higher than that of the liquid electrolytes. The high ionic conductivity is attributable to the unique structure of LGPS, in which lithium ions are distributed along the c-axis in a three-dimensional framework composed of an octahedral LiS6 unit and tetrahedral PS4 and GeS4 units (Kwon et al, 2015;Wang et al, 2015).…”
mentioning
confidence: 99%
“…In addition, the diffraction lines of the LGPS-type phase shift to a lower angle, indicating the lattice expansion of the LGPS-type phase. This behavior could be due to the impurity phase, because the P content in the LGPS-type phases is decreased by Li 3 PO 4 formation, and a higher Ge:P ratio leads to larger lattice parameters [16]. From these results, the solidsolution range for oxygen substitution was found to be limited to within 0 x < 0.9.…”
Section: Resultsmentioning
confidence: 74%
“…Space group P4 2 /nmc was used for the refinements, and the initial parameters were taken from the structural model reported for the LGPS phase [16]. In addition, occupancies, and atomic displacement parameters for the Li atoms were fixed at the values reported from the neutron diffraction data for LGPS.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Janek, Zeier and co-workers [71] confirmed the significant contribution of the in-plane Li diffusion (along Li3 − [Li2 − Li2] − Li3 and Li4 − [Li1 − Li1] − Li4) pathways by neutron powder diffraction combined with a maximum entropy analysis. Hence, they demonstrated that already at room temperature a quasi 3D diffusion mechanism is operative in LGPS, with the 3D character of Li diffusion further increasing at higher T [71,72] (Fig. 6).…”
Section: (I) Structural and Electrochemical Propertiesmentioning
confidence: 99%